2020
DOI: 10.1007/s00330-020-07502-4
|View full text |Cite
|
Sign up to set email alerts
|

Intra-tumoural lipid composition and lymphovascular invasion in breast cancer via non-invasive magnetic resonance spectroscopy

Abstract: Objectives Despite improved survival due to new treatments, the 10-year survival rate in patients with breast cancer is approximately 75%. Lymphovascular invasion (LVI), a prognostic marker independent from histological grade and stage, can only be fully determined at final histological examination. Lipid composition is deregulated in tumour via de novo lipogenesis, with alteration in lipogenic genes in LVI. We hypothesise alteration in lipid composition derived from novel non-invasive spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 43 publications
(75 reference statements)
0
12
0
Order By: Relevance
“…Except for lactic acid, carbonic anhydrase 9 (CA-9), maintaining the acidic condition of TME, also contributed to the tumor progression ( 38 ). Interestingly, the lipid composition in TME is also an important factor for macrophages recruitment and functional remolding ( 39 ). In our study, by using the co-culturing system in vitro , we find that the recruitment of macrophages is strongly enhanced by LDHA.…”
Section: Discussionmentioning
confidence: 99%
“…Except for lactic acid, carbonic anhydrase 9 (CA-9), maintaining the acidic condition of TME, also contributed to the tumor progression ( 38 ). Interestingly, the lipid composition in TME is also an important factor for macrophages recruitment and functional remolding ( 39 ). In our study, by using the co-culturing system in vitro , we find that the recruitment of macrophages is strongly enhanced by LDHA.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the previous two imaging methods, breast MRI is the most sensitive and accurate imaging method for preoperative staging of breast cancer, and its sensitivity for tumor diagnosis is not affected by the density [ 11 , 67 ]. MRI provides information indicating tumor biological function: spectral imaging can determine the function of chemical components within tissue regions for qualitative tumor diagnosis through metabolite detection [ 68 ]; or MRI spectral imaging can be used for quantitative assessment of lipid composition in the breast based on altered adipogenesis genes in breast cancers with vascular infiltration, allowing prediction of tumor vascular infiltration events [ 69 ], assessment of chemotherapy response [ 70 ], and subtype identification [ 71 ]. Diffusion-weighted imaging (DWI) is highly sensitive for breast cancer as it reveals and evaluates local pathophysiological features by measuring the mobile phase of water molecules in the tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the study has found that LVI is an independent predictor of survival in breast cancer after neoadjuvant chemotherapy, some scholars also have found that the occurrence of LVI is significantly related to luminal B with HER2(-), and the basal-like subtype [ 20 ]. Cheung SM and Bo Bae Choi et al considered that preoperative magnetic resonance imaging (MRI) and diffusion-weighted imaging (DWI) can help diagnose the existence of LVI in breast cancer [ 21 , 22 ]. Actually, in our multivariate analysis about HR+ population, patients with LVI had the strongest independent association with residual positive axillary LNs (OR, 6.438; P < 0.05).…”
Section: Discussionmentioning
confidence: 99%